PRINCIPLES AND EXAMPLES OF DESIGN OF REHABILITATION CENTERS IN RUSSIA AND ABROAD - Zvyagintseva, Marina; Skripkina, Julia; Fedorchenko, Natalia (Journal of Applied Engineering Science, 2019)
This article examines and analyzes the design features of rehabilitation and medical centers in Russia and Europe. The principles of formation of constructive, functional and aesthetic, as well as economic, social and environmental aspects of the development of projects of rehabilitation centers are revealed. The interrelation and influence of architecture on the process of treatment of patients during rehabilitation is shown. On the basis of foreign and Russian experience, conclusions are drawn about the design and design of rehabilitation centers, which take into account the developed project of the health and rehabilitation center.
Keywords: architectural solution; medical institution; comfortable environment; rehabilitation